Serological and Molecular Identification of Chickpea chlorotic stunt virus from Chickpea in Iran - Bananej, K (Plant disease, 2010)
During a survey of chickpea (Cicer arietinum L.) crops in western Iran in July 2009, leaf samples from yellow and stunted plants were collected from fields in the provinces of Kermanshah (n = 30) and Lorestan (n = 16). Symptoms suggested infections by luteoviruses, such as viruses of the Beet western yellows virus (BWYV) subgroup (e.g., Turnip yellows virus [TuYV]) (4) and Chickpea chlorotic stunt virus (CpCSV), a virus first described from Ethiopia (1) and recently reported from other countries of West Asia and North Africa (2). All 46 samples were analyzed by triple-antibody sandwich (TAS)-ELISA (3) using the luteovirus-specific monoclonal antibody (MAb) B-2-5G4 (1), a mixture of three MAbs (1-1G5, -3H4, and -4B12) to an Ethiopian (Eth) isolate of CpCSV (1), and six individual MAbs (5-1F10, -2B8, -3D5, -5B8, -6F11, and 6-4E10) to a CpCSV isolate from Syria (Sy) (2) in combination with a mixture of polyclonal antibodies to CpCSV and BWYV for plate coating. CpCSV-Eth and -Sy were used as positive controls. Six of the sixteen Lorestan samples and two of the thirty Kermanshah samples reacted with MAb B-2-5-G4, indicating infections with a luteovirus. While none of the 46 samples reacted with the mixture of the CpCSV-Eth specific MAbs, two (Lorestan No. 25 and Kermanshah No. 31) of the eight MAb B-2-5-G4-positive samples reacted strongly with each of the six individual MAbs to CpCSV-Sy. Since this indicated the presence of a serotype II isolate of CpCSV in these two chickpea samples from Iran, we tried to confirm this by reverse transcriptase (RT)-PCR. TRI-Reagent (Sigma, St. Louis, MO) was used for total RNA extraction from samples Nos. 25 and 31. RT-PCR was carried out using the primers 5'-CAC GTG AGA TCA ATA GTC AAT GAA TAC GGT CG-3' (sense) and 5'-TTT GTA ATT ACC AAY ATT CCA-3' (antisense) derived from the CpCSV coat protein (CP) gene and 5' end of ORF5, the readthrough domain (RTD), respectively. In RT-PCR experiments, no amplification was observed from healthy plant extracts, but chickpea samples Nos. 25 and 31 yielded amplicons of ~1,100 bp, which were used for cloning and sequencing. The sequences of the complete CP gene and 5' end of ORF5 (RTD) from the two samples were determined and deposited in GenBank (GU930837 and GU930838). Sequence analysis revealed that the two Iranian isolates were most similar to each other, sharing CP nucleotide and amino acid (aa) sequence identities of 97.8 and 99.1%, respectively. They differed from each other only in 3 of the 200 aa positions of their CP sequences and were indistinguishable in the 128 N-terminal aa positions of their RTD sequences. When using DNAMAN for phylogenetic analysis, they clustered with serogroup-II isolates of CpCSV from Egypt, Morocco, and Syria (2), with which they were most closely related (approximately 98% in CP aa sequence). While the two Iranian CpCSV isolates differed by approximately 10% in CP aa sequences from serotype-I isolates of CpCSV, they differed strikingly (by ~27%) in RTD aa sequences from CpCSV-Eth, a serotype-I isolate and the only CpCSV isolate for which RTD sequences are available. To our knowledge, this is the first report of the occurrence of CpCSV in Iran. The virus can cause yellowing and stunting of chickpea similar to symptoms caused by other viruses reported from this crop. References: (1) A. D. Abraham et al. Phytopathology 96:437, 2006. (2) A. D. Abraham et al. Arch. Virol 154:791, 2009. (3) A. Franz et al. Ann. Appl. Biol. 128:255, 1996. (4) K. M. Makkouk et al. J. Plant Dis. Prot. 110:157, 2003